1996
DOI: 10.1128/aac.40.10.2321
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of topoisomerase IV and DNA gyrase as ciprofloxacin targets in Streptococcus pneumoniae

Abstract: Ciprofloxacin-resistant mutants of Streptococcus pneumoniae 7785 were generated by stepwise selection at increasing drug concentrations. Sequence analysis of PCR products from the strains was used to examine the quinolone resistance-determining regions of the GyrA and GyrB proteins of DNA gyrase and the analogous regions of the ParC and ParE subunits of DNA topoisomerase IV. First-step mutants exhibiting low-level resistance had no detectable changes in their topoisomerase quinolone resistance-determining regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
189
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(209 citation statements)
references
References 37 publications
16
189
1
3
Order By: Relevance
“…If the frequency of resistant subpopulations after treatment with each fluoroquinolone had increased, the susceptibility of the colonies obtained on the plate containing the fluoroquinolone, and gene mutations in the quinolone resistance-determining regions (QRDRs) of gyrA and parC of representative colonies, were investigated. The QRDRs of gyrA and parC were amplified using the polymerase chain reaction (PCR), following the method of Pan et al 3 DNA sequences were determined with an ABI Prism 310 DNA sequencer (Applied Biosystems, Foster City, CA, USA), and were analyzed with DNASIS sequence analysis programs (ver. 2.1, Hitachi Software Engineering, San Francisco, CA, USA).…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the frequency of resistant subpopulations after treatment with each fluoroquinolone had increased, the susceptibility of the colonies obtained on the plate containing the fluoroquinolone, and gene mutations in the quinolone resistance-determining regions (QRDRs) of gyrA and parC of representative colonies, were investigated. The QRDRs of gyrA and parC were amplified using the polymerase chain reaction (PCR), following the method of Pan et al 3 DNA sequences were determined with an ABI Prism 310 DNA sequencer (Applied Biosystems, Foster City, CA, USA), and were analyzed with DNASIS sequence analysis programs (ver. 2.1, Hitachi Software Engineering, San Francisco, CA, USA).…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…[1][2][3][4] For a long time penicillin was the most effective drug against such infections. However, penicillin-resistant S. pneumoniae was first reported in 1967, followed by the report that the frequency of isolation of penicillin-nonsusceptible strains of S. pneumoniae increased dramatically during the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) was used to amplify the QRDRs in gyrA, gyrB, parC and parE using previously described primer pairs and cycling conditions [12]. Template DNA was prepared using Genomic DNA Isolation Solution (NucleoGen Inc., Siheung, South Korea) following the manufacturer's instructions.…”
Section: Quinolone Resistance-determining Region (Qrdr) Sequence Analmentioning
confidence: 99%
“…For example, selection in vitro has shown that a first-step mutation in topoisomerase IV confers low-level resistance to ciprofloxacin, levofloxacin and ofloxacin, while low-level resistance to sparfloxacin, moxifloxacin and gatifloxacin is the result of a first-step mutation in DNA gyrase [52][53][54][55]. In the case of clinafloxacin, DNA gyrase and topoisomerase IV are targeted equally [56].…”
Section: Natural Selectionmentioning
confidence: 99%